Biomimetic platelet-camouflaged drug-loaded polypyrrole for the precise targeted antithrombotic therapy - Zhining Zhao; Xiaodan Li; Yan Wang; Cheng Liu; Guixia Ling; Peng Zhang (Journal of Nanobiotechnology, 2023)
Abstract Lower extremity deep venous thrombosis (LEDVT) affects patient’s quality of life for a long time, and even causes pulmonary embolism, which threatens human health. Current anticoagulant drugs in clinical treatment are hampered by the risk of bleeding due to poor targeting and low drug penetration. Here, we used platelet (PLT)-like biological targeting to enhance the delivery and accumulation of nanomedicines in thrombus and reduce the risk of bleeding. Meanwhile, the parallel strategy of “thrombus thermal ablation and anticoagulation” was applied to increase the permeability of drugs in thrombus and achieve the optimal antithrombotic effect. Polypyrrole (PPy) and rivaroxban (Riv, an anticoagulant drug) were co-assembled into platelet membrane-coated nanoparticles (NPs), PLT-PPy/Riv NPs, which actively targeted the thrombotic lesion at multiple targets in the platelet membrane and were thermally and drug-specific thrombolysed by 808 nm laser irradiation. The combination therapy resulted in up to 90% thrombolysis in a femoral vein thrombosis model compared to single phototherapy or drug therapy. The results showed that the nanoformulation provided a new direction for remote precise and controlled sustained thrombolysis, which was in line with the trend of nanomedicine towards clinical translation.